Leprosy, Lepers and Leprosariums in Medieval Italy. Management of Assistance, Daily Life and Religious Experiences in Documents and Narration (Studi di storia medioevale e di diplomatica - Nuova Serie, 2019)
This contribution is aimed at presenting the different phases of a research project entitled Leprosy, Lepers and Leprosaria in Medieval Italy. The Management of Charit, Daily Life and Religious Experiences in Documents and Narrative. The project has become necessary because, unlike the case of more generalized research on hospitals, in which Italian historians have continued maintain a high level of innovation in terms of topics and methodologies, since the early 1990s the scholarship in Italy on lepers and leper hospitals has seen a sharp decline in the number of works and a move away from the interdisciplinary approach that has characterized the numerous studies that have appeared in Europe and especially in France. The project aims to provide a map of Italian leproseries between the 12th- 14th centuries and, at the same time, to create an edition of thirteenth century documents of Verona’s leper hospital S. Giacomo alla Tomba, which constitutes a case-study in Italy’s panorama of documents.
Keywords: history of Leprosy; history of Charity in the Middle Ages; history of Religious Life in the Middle Ages